The effect of corporate social responsibility disclosures on financial performance in the banking industry: empirical study on Egyptian banking sector - Racha El Moslemany (International Journal of Business & Economic Development, 2017)
The aim of this paper to establish the relationship between corporate social responsibility disclosure and financial performance in the Egyptian banking sector. Only three banks were included in the study because Corporate Social Responsibility is a new concept that has not yet been fully established in the banking sector in Egypt. Secondary data were obtained from the annual financial reports of the banks for the period from 2008 to 2011. Corporate social responsibility score was obtained using content analysis of reports of the companies on various components of corporate social responsibility as reported in their annual financial reports. The present study identified four dimensions in the pilot study: Environment, Community, Customer, and Employee. Descriptive analysis was used to describe data collected such as Pearson correlation method. The authors used regression analysis to study the relationship between the dependent variables and the independent variables and the bank age and bank size were used as control variables in the analysis. The results indicated an insignificant relationship between the independent variables (corporate social responsibility toward environment, community, customer, and employee) used in the model and the dependent variables Corporate Financial Performance as measured by (ROA, ROE, NPM, and EPS). The results of the study proved the absence of a significant relationship between the dependent and the independent variables as a whole. Yet, some relationships were found concerning individual measures. The major limitation of this paper is the sample size. In addition, failure of corporations to disclose CSR in the annual reports will have a material effect on these findings. The findings of this paper have practical implications on the management of Banks in Egypt to re-think and re-strategize their CSR policies that incorporate social and economic performance to improve their CFP.